Strategi Politik Meraih Dukungan Massa Pondok Pesantren: Studi Kasus Bentuk Komunikasi Politik Calon Legislatif DPR RI Daerah Pemilihan Jember dan Lumajang pada Pemilihan Legislatif 2014: Political Strategies to Gain Support from Islamic Boarding School Masses: A Case Study of Political Communication Forms by Legislative Candidates of the Indonesian House of Representatives in the Jember and Lumajang Electoral Districts During the 2014 Legislative Election - Kun Wazis (Fenomena, 2015)
This qualitative research describes the struggle of politicians from Jember and Lumajang who applied political communication models. To become a winner in the parliamentary election in Jakarta, the politicians utilized Islamic boarding school masses as a political force. There were choices among political rhetoric, political agitation, political public relations, political propaganda, political campaigns, political lobbying, and political behavior to approach the Islamic boarding school masses, such as kyai and santri. All politicians believed that the Islamic boarding school masses possessed political power for their success. The politicians from the National Democrat (Nasdem) Party, the National Awakening Party, the Indonesian Democratic Party of Struggle, the Golkar Party, the Great Indonesia Movement (Gerindra) Party, the Democratic Party, and the National Mandate Party applied differentiated political strategies to persuade the Islamic boarding school masses. Penelitian kualitatif ini menggambarkan perjuangan politisi dari Jember dan Lumajang yang menerapkan model komunikasi politik. Untuk menjadi pemenang di parlemen Jakarta, politisi menggunakan massa pondok pesantren sebagai kekuatan politik. Terdapat pilihan antara retorika politik, agitasi politik, hubungan masyarakat politik, propaganda politik, kampanye politik, lobi politik, dan perilaku politik untuk mendekati massa pondok pesantren, seperti kyai dan santri. Semua politisi percaya bahwa massa pondok pesantren memiliki kekuatan politik untuk keberhasilan tujuan mereka. Para politisi dari Partai Nasional Demokrat (Nasdem), Partai Kebangkitan Bangsa, Partai Demokrasi Indonesia Perjuangan, Partai Golkar, Partai Gerakan Indonesia Raya (Gerindra), Partai Demokrat, dan Partai Amanat Nasional menerapkan strategi politik yang berbeda untuk membujuk massa pondok pesantren.